A study on the medicinal value and distribution of climbers of Nattika, India - Abhilash, ES; Parayil, Sheeja P; Raju, AR; Sathian, Brijesh; Udayan, Vinil (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
Seventeen climber species were collected from Nattika which is highly medicinal in nature. Five Climber species represented with high density, five with medium density and seven with low density respectively. The wild areas of the Nattika harbor some of the rare species that are not seen in adjacent lands. This study throws light to the importance of conservation of wild areas and also suggests that peoples will be benefited by sustainable use of medicinal plants. DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9510 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1: 36-39